Strategy for Improving Passport Service Quality Through Interpersonal Communication and Information Technology Utilization at South Jakarta Special Class I Non-Checkpoint Immigration Office - Mulyawan, Budy; Firlana, Habbi; Wibowo, Pascalis Danny Kristi; Adillah, Muhammad Arief (Dinasti International Journal of Management Science, 2025)
This study aims to analyze the simultaneous and partial influence of Officer Interpersonal Communication and Information Technology Utilization on the Quality of Passport Services at South Jakarta Special Class I Non-Checkpoint Immigration Office. The quality of public services in the digital age demands synergy between technological efficiency and the humanism of interaction, which is the background that prompted this research. The method used is a mixed methods approach with data collected from 284 respondents. The regression test results show that both variables positively and significantly influence Service Quality, with a contribution of 87.7%. Partially, the Utilization of Information Technology is proven to be the more dominant factor in determining applicant satisfaction. Nevertheless, descriptive analysis and qualitative findings identified Interpersonal Communication, particularly the aspect of Empathy, as a major weakness most frequently cited by applicants, necessitating specific communication adaptation training. In conclusion, to achieve excellent service, the necessary strategy is a balanced one that leverages technological dominance for efficiency while also investing in improving staff empathy to create supportive and accountable interactions.